QUALITY OF LIFE AND PSYCHO-EMOTIONAL STATUS IN PATIENTS WITH PSORIATIC ARTHRITIS - Uralov Rustam Sherbekovich; Eshmuratov Sardor Eldorovich (Ta'lim innovatsiyasi va integratsiyasi, 2025)
The dynamics of quality of life (QOL) and psychoemotional status in patients with psoriatic arthritis (PA) under the influence of basic therapy with methotrexate (n=28)  and  sulfasalazine  (n=20)  were  studied.  The  control  group  consisted  of  25 patients receiving only nonsteroidal anti-inflammatory drugs. Therapy with basic drugs in patients with PA leads to a rapid and long-lasting clinical effect, improves the quality of life of patients according to the SF-36 questionnaire. The positive effect of basic therapy on depression symptoms is not always pronounced and is significant only in the methotrexate group.